1994
DOI: 10.1111/j.1432-1033.1994.tb18843.x
|View full text |Cite
|
Sign up to set email alerts
|

No intermediate channelling in stepwise hydrolysis of fluorescein di‐β‐D‐galactoside by β‐galactosidase

Abstract: In the enzymic hydrolysis of biopolymers such as polypeptides, polysaccharides or nucleic acids, two extreme patterns of action are conceivable [l]. The enzyme, after forming an enzyme-substrate complex, may begin to catalyze hydrolysis of mult.iple bonds in what has been described as zipper fashion until it comes to the end of the chain. Alternatively, the hydrolysis of only one bond per effective encounter is catalyzed, the classical random action. Between these extremes is the case of 'multiple attack', whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…Fluorescein-di-β- d -galactopyranoside (FDG, Figure 1) is a fluorogenic compound that is non-fluorescent until it is hydrolyzed by β-galactosidase in the cytoplasm of Escherichia coli to produce a highly fluorescent dye, fluorescein [19], [20], [21]. We first confirmed that both FDG and fluorescein are substrates of RND pumps in E. coli .…”
Section: Introductionmentioning
confidence: 64%
“…Fluorescein-di-β- d -galactopyranoside (FDG, Figure 1) is a fluorogenic compound that is non-fluorescent until it is hydrolyzed by β-galactosidase in the cytoplasm of Escherichia coli to produce a highly fluorescent dye, fluorescein [19], [20], [21]. We first confirmed that both FDG and fluorescein are substrates of RND pumps in E. coli .…”
Section: Introductionmentioning
confidence: 64%
“…Fluorescein-di-β- D -galactopyranoside (FDG) is hydrolyzed in the cytoplasm of E. coli by β-galacotsidase to produce fluorescein ( Russo-Marie et al, 1993 ; Fieldler and Hinz, 1994 ; Yang and Hu, 2004 ). Both FDG and fluorescein were shown to be efflux-pump substrates and could be used to develop transport assays with E. coli cells expressing the pseudomonal MexAB-OprM and MexXY-OprM efflux systems ( Matsumoto et al, 2011 ).…”
Section: Efflux Assaysmentioning
confidence: 99%
“…We utilized an appropriate substrate, fluorescein-di-β- d -galactopyranoside (FDG), for a visual assay. FDG is non-fluorescent until it is hydrolysed by β-galactosidase in the cytoplasm of Escherichia coli to produce a highly fluorescent dye, fluorescein (Russo-Marie et al, 1993; Fieldler and Hinz, 1994; Yang and Hu, 2004). We confirmed that both FDG and fluorescein are substrates of RND pumps in E. coli .…”
Section: Introductionmentioning
confidence: 99%